Soccer - Wendorff, Anne. (Minneapolis, MN : Bellwether Media, 2010)
"Simple text and full color photographs introduce beginning readers to the sport of soccer. Developed by literacy experts for students in grades two through five"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Soccer -- Juvenile literature